Optimalisasi Karakteristik Individu Untuk Meningkatkan Kinerja Karyawan Kepada Sai Coffee and Space - Ni Made Satya Utami; Ni Made Rika Monika (Jurnal Inovasi Pengabdian Masyarakat, 2025)
This community service program aimed to enhance the effectiveness and security of the digital stock-checking system at Sai Coffee and Space. The identified problems included employees’ lack of understanding of the digital stock system, the slow process of manual checking, and the risk of stock accumulation. The implementation methods involved observation, system evaluation, employee training, and the application of an innovative cashier system. The results demonstrated significant improvements in stock-checking efficiency, reduction of stockpile risks, and greater flexibility in stock-checking methods. However, several challenges remained, such as technical constraints and employees’ limited understanding of the system. It is recommended to conduct regular training, continuous monitoring, and consistent stock validation to ensure the sustainability of the program